Too marvelous for words : the life and genius of Art Tatum - Lester, James (Oxford University Press, 1994)
Art Tatum defined the limits of the possible in jazz piano. Gunther Schuller called Tatum's playing "a marvel of perfection ... His deep-in-the-keys full piano sonority, the tone and touch control in pyrotechnical passages ... are miracles of performance." Whitney Balliett wrote "no pianist has ever hit notes more beautifully. Each one - no matter how fast the tempo - was light and complete and resonant, like the letters on a finely printed page." His famous runs have been.